Vologaeses as Mirror - Clark, Anna J. (Histos, 2011)
This paper explores how, like other 'barbarian' leaders in Roman historiography who have received more extensive scholarly interest, the Parthian king Vologaeses is presented in Ann. 15.1–2 and 15.15 as, amongst other things, a kind of mirror for the Julio-Claudian emperors who are the principal foci of the Annals. The images Vologaeses offers are refractions rather than specular reflections. The ways in which he is depicted and the claims put into his mouth encourage the reader to think of earlier leaders, Roman and non-Roman, and, variously, of all the Roman emperors treated by Tacitus in his Annals, and thus to reflect further on crucial general Tacitean themes: the nature of the principate and of Rome itself under different individuals and one family; the differences between past and present; and decision-making and its agency in imperial Rome. The opening chapters of Annals 15 have often been thought of as somehow anomalous in their position: one suggestion is offered as to why, on the contrary, they might be considered to have been carefully placed.